Além das palavras : uma exploração filosófica do consentimento sexual e suas implicações epistêmicas - Lourenço, Myllana Aguiar da Silva (2024)
Consent is a widely used concept, especially in feminist discussions, for analyzing sexual contexts, particularly to distinguish legitimate sexual relations from sexual abuses. Therefore, this paper is dedicated to investigating the issues and adequacy of this concept, starting from the scope of social epistemology and philosophy of language, which are areas strongly related and complement each other in various ways. Drawing from Feminist Philosophy of Language, we seek a definition for consent as a speech act, investigating the manner of its communication and the possibility of silencing female consent in patriarchal contexts, highlighting cases of bad sex. We link the discussion with epistemic consequences, raising questions about epistemic responsibility and the sufficiency of consent communication for the permissibility of sexual acts. Lastly, we introduce the theory of Epistemic Injustices in the field of Social Epistemology, as a theory that provides important tools for analyzing the impact of social hierarchies on communication, understanding how distortion of uptake and credibility is possible. We employ a method of literature review and conceptual analysis, investigating proposals from each area along with their respective criticisms and established relations. As a result, we understand sexual consent to be a speech act whose illocutionary force element is a mental state of relinquishing the right for an action not to occur; furthermore, this act needs to be communicated, as it involves a moral obligation. Thus, we note that the communication of sexual consent is necessary but not sufficient, and the epistemic responsibility to ensure correct uptake lies with the agent with more social power. Finally, we demonstrate that social prejudices can distort communication and credibility attribution, causing significant impacts on female sexual consent. This work aims to contribute to the reflection on the topic and gathering existing literature, particularly as it is predominantly available in English. The conclusions may be fruitful for a more appropriate analysis of sexual abuses, pornography, and prostitution, particularly regarding the female condition in these situations. Social epistemology and philosophy of language have proven to be fruitful fields in providing explanatory resources for phenomena of oppression.